2014
DOI: 10.1039/c4fo00290c
|View full text |Cite
|
Sign up to set email alerts
|

Variations in caffeine and chlorogenic acid contents of coffees: what are we drinking?

Abstract: This paper reports on the wide variations in the caffeine and chlorogenic acid contents of coffees purchased in Scotland, Spain and Italy. Image © Shutterstock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
152
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(177 citation statements)
references
References 28 publications
19
152
2
4
Order By: Relevance
“…Dose response and tolerance to regular consumption vary between individuals; so, for some people, even a single cup may cause sleeplessness with a racing mind, while for others, drinking ten times this amount can still be pleasant and not interfere with sleep [6]. Caffeine has a half-life of approximately 4-6 h, with a plasma peak time concentration following it ingestion between 30-60 minutes (average 40) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose response and tolerance to regular consumption vary between individuals; so, for some people, even a single cup may cause sleeplessness with a racing mind, while for others, drinking ten times this amount can still be pleasant and not interfere with sleep [6]. Caffeine has a half-life of approximately 4-6 h, with a plasma peak time concentration following it ingestion between 30-60 minutes (average 40) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly acts upon the central nervous system, with widely known physiological and psychological effects (increased alertness, enhanced vigilance, reduced fatigue) [1][2][3][4][5][6]. All its effects are through the antagonism of the A1 and A2 subtypes of the adenosine receptor, potentiating the effects of sympathetic nervous system stimulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Because of these many positive influences on human body, since the middle of the 19 th century, when the first references about CGAs appeared, there have been a high amount of articles dealing with extraction and detection techniques of CGAs or studying their influence on human health. CGAs have been observed and isolated in many plant materials such as coffee 9 , apple 10 , tomato, papaya 11 , sweet potato 12 , prune 13 , pear 14 , cabbage 15 , yacon 16 , burdock 17 , cherry 18 , apricot 19 , orange 20 , etc. Coffee beans are undoubtedly the most common observed matrix because coffee is the main source of CGAs.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyhydroquinone is a compound that is generated from the roasting of coffee beans [28]. Direct measurements of commercially available brewed coffee showed that less than 200 mg chlorogenic acids is generally contained in one serving [37]. The beverages were manufactured industrially (Kao Co. Tokyo, Japan) and were taste-and flavor-matched (coffee-flavored).…”
Section: Test Beveragesmentioning
confidence: 99%